2009
DOI: 10.1073/pnas.0907689106
|View full text |Cite
|
Sign up to set email alerts
|

Probing PML body function in ALT cells reveals spatiotemporal requirements for telomere recombination

Abstract: Promyelocytic leukemia (PML) bodies (also called ND10) are dynamic nuclear structures implicated in a wide variety of cellular processes. ALT-associated PML bodies (APBs) are specialized PML bodies found exclusively in telomerase-negative tumors in which telomeres are maintained by recombination-based alternative (ALT) mechanisms. Although it has been suggested that APBs are directly implicated in telomere metabolism of ALT cells, their precise role and structure have remained elusive. Here we show that PML bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
125
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(144 citation statements)
references
References 34 publications
12
125
0
Order By: Relevance
“…We found here that APB assembly in U2OS cells was inhibited by an 'open' telomeric chromatin state, as the knockdown of several repressive chromatin modifiers, as well as chromatin decondensation initiated by HDAC inhibition or HMGN5 recruitment, resulted in a The formation of a PML subcompartment at telomeres induces telomeric chromatin compaction and clustering of telomeres, and possibly also ECTRs, as proposed previously (Cho et al, 2014;Draskovic et al, 2009). As a result of APB formation, TRF2 becomes partly depleted at associated telomeres.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…We found here that APB assembly in U2OS cells was inhibited by an 'open' telomeric chromatin state, as the knockdown of several repressive chromatin modifiers, as well as chromatin decondensation initiated by HDAC inhibition or HMGN5 recruitment, resulted in a The formation of a PML subcompartment at telomeres induces telomeric chromatin compaction and clustering of telomeres, and possibly also ECTRs, as proposed previously (Cho et al, 2014;Draskovic et al, 2009). As a result of APB formation, TRF2 becomes partly depleted at associated telomeres.…”
Section: Discussionsupporting
confidence: 76%
“…5). First, formation of a PML subcompartment at telomeres induces telomeric chromatin compaction and clustering of telomeres, and possibly also ECTRs, as proposed previously (Cho et al, 2014;Draskovic et al, 2009). Second, as a result of APB formation, TRF2 becomes partly depleted at associated telomeres.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Others have found that disruption of APBs prevents telomere maintenance by ALT and leads to loss of culture viability, arguing for an active role of APBs in telomere maintenance by ALT (Jiang et al, 2005). The spatio-temporal dynamics of telomeric DNA association with PML bodies have been recently described, and the authors of this study conclude that telomere recombination takes place in these structures (Draskovic et al, 2009). Furthermore, new PML bodies form at telomeric DNA regardless of which TMM is active (Brouwer et al, 2009) and APBs form transiently in human diploid fibroblasts following high LET radiation (Berardinelli et al, 2010), suggesting that the association of telomeric DNA with PML bodies may be a component of a DNA damage response.…”
Section: Altsupporting
confidence: 51%
“…6A). hTR localization with ALT-associated PML bodies (APBs) could also occur because APBs are formed by the coalescence of extremities with long and short telomeres (Draskovic et al, 2009). Localization of hTR to telomeres in h/h5 cells suggests that the telomerase complex in these cells can be recruited to telomeres.…”
Section: Chimeric Tert-tr Complexes Fail To Localize To the Telomeresmentioning
confidence: 99%